The Effect of Local Taxes, General Allocation Funds, and Special Allocation Funds on Capital Expenditures of the Government of South Sumatra Province 2010 - 2019 - Ayunda Dina Maharani; Harsi Romli; Vhika Meiriasari (International Journal of Community Service & Engagement, 2021)
This study aims to examine the effect of local taxes, general allocation funds and special allocation funds on the capital expenditure of the South Sumatra Province government for the 2010-2019 period. The data used in this study are primary and secondary. Furthermore, the data were analyzed using multiple linear regression. This study prove that the general allocation funds have a positive effect on the capital expenditure of the South Sumatra provincial government. While, local taxes and special allocation funds are not proven to have a positive effect on the capital expenditure of the South Sumatra provincial government. Furthermore, the test results of the coefficient of determination (R2) obtained a value of 0,773. This shows that the amount of the contribution of the tax variables, general allocation funds and special allocation funds can explain the capital expenditure of 77,30% the remaining is influenced by other variables included in this study.